2005
DOI: 10.1103/physrevd.71.065005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of CPT and Lorentz invariance violation on pulsar kicks

Abstract: The breakdown of Lorentz's and CPT invariance, as described by the Extension of the Standard Model, gives rise to a modification of the dispersion relation of particles. Consequences of such a modification are reviewed in the framework of pulsar kicks induced by neutrino oscillations (activesterile conversion). A peculiar feature of the modified energy-momentum relations is the occurrence of terms of the form δΠ ·p, where δΠ accounts for the difference of spatial components of flavor depending coefficients whi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 79 publications
0
22
0
Order By: Relevance
“…Nonetheless, it suffices to reproduce the data for atmospheric neutrinos via Eq. (18). The other degree of freedom in the two coefficientsk (p) ,c (q) determines the onset of the Lorentz-violating seesaw.…”
Section: Atmospheric Neutrinosmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, it suffices to reproduce the data for atmospheric neutrinos via Eq. (18). The other degree of freedom in the two coefficientsk (p) ,c (q) determines the onset of the Lorentz-violating seesaw.…”
Section: Atmospheric Neutrinosmentioning
confidence: 99%
“…The interferometric nature of particle oscillations suggests that sensitive neutrino or neutralmeson experiments might well yield the first detectable signals of tiny Lorentz violation. In the neutrino sector, recent SME-based phenomenological studies [8,9,[16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] and methodologies for experimental analysis [34,35] have spurred searches for Lorentz and CPT violation by the LSND [36], Super-Kamiokande (SK) [37], MINOS [38,39], MiniBooNE [40], and IceCube collaborations [41]. Searches have also been performed with neutral mesons [42,43], and recent D0 results suggest some evidence for anomalous CP violation [44] that could be attributed to Lorentz and CPT violation [45].…”
Section: Introductionmentioning
confidence: 99%
“…A few consider also anisotropic effects [13,[34][35][36][37][38]. Here, we treat the general case, allowing all components of (a L ) α ab and (c L ) αβ ab to be nonzero.…”
Section: Introductionmentioning
confidence: 99%
“…29It has recently been suggested that Lorentz violation might play a role in the formation of the pulsar itself, specifically in large pulsar anomalous velocities [192]. …”
mentioning
confidence: 99%